Factors influencing virtual lab adoption in marginalized rural schools: insights from South Africa - Brian Shambare; Thuthukile Jita (Smart Learning Environments)
Abstract Teaching in rural schools is frequently marked by challenges ranging from restricted technological infrastructure and geographical remoteness to sparse professional development. Guided by the Unified Theory of Acceptance and Use of Technology (UTAUT), this paper reports findings from a sequential explanatory mixed-methods study that investigated Virtual Lab (VL) adoption in rural South African schools. Data collected through a questionnaire (N = 186) and semi-structured interviews (N = 4) involving life sciences teachers were analysed using descriptive statistics and thematic analysis. The study revealed surprising trends in VL adoption, indicating that family and friends have a greater influence than colleages. Contrary to conventional wisdom on teacher motivation, this paper underscores learners’ enthusiasm as pivotal. Despite reservations regarding facilitating conditions, improved technology access challenges prior assumptions of scarcity in rural schools. Nevertheless, while challenges such as low competence and inadequate professional development persist, rural school teachers express readiness for adoption, signalling potential increased usage under favourable conditions.